2019
DOI: 10.1016/j.ebiom.2019.01.058
|View full text |Cite
|
Sign up to set email alerts
|

POH1 contributes to hyperactivation of TGF-β signaling and facilitates hepatocellular carcinoma metastasis through deubiquitinating TGF-β receptors and caveolin-1

Abstract: Background Hyper-activation of TGF-β signaling is critically involved in progression of hepatocellular carcinoma (HCC). However, the events that contribute to the dysregulation of TGF-β pathway in HCC, especially at the post-translational level, are not well understood. Methods Associations of deubiquitinase POH1 with TGF-β signaling activity and the outcomes of HCC patients were examined by data mining of online HCC datasets, immunohistochemistry analyses using human H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 49 publications
2
37
0
1
Order By: Relevance
“…Alternatively, EGF treatment induces caveola-dependent endocytosis of plasma membrane E-cadherin/β-catenin complex, disrupts cell-cell Non-membrane-bounded organelle + Cell projection + Joshi et al [71] Cytoplasmic vesicle + Fridolfsson et al [44] Lipid particle + Fridolfsson et al [44] contacts, downregulates E-cadherin as well as CAV1, and thereby promotes invasion of cancer cells [99]. Moreover, CAV1 has been proposed to inhibit TGF-β signaling, via caveolae/membrane raft-mediated endocytosis and lysosomal degradation of TGF-β receptors [28,175]. On the one hand, CAV1 interacts with TGF-β receptors, abolishing their interaction with SMAD proteins and downstream events [28].…”
Section: Cav1 As a Tumor Suppressor Or Promotermentioning
confidence: 99%
“…Alternatively, EGF treatment induces caveola-dependent endocytosis of plasma membrane E-cadherin/β-catenin complex, disrupts cell-cell Non-membrane-bounded organelle + Cell projection + Joshi et al [71] Cytoplasmic vesicle + Fridolfsson et al [44] Lipid particle + Fridolfsson et al [44] contacts, downregulates E-cadherin as well as CAV1, and thereby promotes invasion of cancer cells [99]. Moreover, CAV1 has been proposed to inhibit TGF-β signaling, via caveolae/membrane raft-mediated endocytosis and lysosomal degradation of TGF-β receptors [28,175]. On the one hand, CAV1 interacts with TGF-β receptors, abolishing their interaction with SMAD proteins and downstream events [28].…”
Section: Cav1 As a Tumor Suppressor Or Promotermentioning
confidence: 99%
“…The deubiquitinase (DUB) 26S proteasome non-ATPase regulatory subunit 14 (PSMD14, RPN11 or POH1), belongs to the JAMM domain metalloprotease family of DUBs and is an important part of 19S regulatory cap in 26S proteasome [5]. PSMD14 has been confirmed to play vital roles in gene ontology and related pathway, including protein stability [6], tumour formation [7], transcriptional regulation [8], double-strand DNA break repair [9], senescence [10], apoptosis and resistance [11], growth and metastasis [5], BMP6 signaling [6], TGF-β signaling [8]. Recently, PSMD14 has been overexpressed in many human cancers, such as HCC, colorectal cancer, multiple myeloma, esophageal squamous cell carcinoma and breast cancer, which it This is related to the poor prognosis of the patients [5,6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PSMD14 inhibits degradation of GRB2 by deubiquitinating this oncoprotein and stabilizing GRB2, which it enhances hepatocellular carcinoma growth and metastasis [5]. POH1 deubiquitinates the TGF-β receptors and CAV1, contributes to hyperactivation of TGF-β signaling and facilitates hepatocellular carcinoma metastasis, which it negatively regulates lysosome pathway-mediated turnover of TGF-β receptors [8]. However, other mechanisms of the contribution of PSMD14 in the progression of HCC remained to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…The deubiquitinase (DUB) 26S proteasome non-ATPase regulatory subunit 14 (PSMD14, RPN11 or POH1), belongs to the JAMM domain metalloprotease family of DUBs and is an important part of 19S regulatory cap in 26S proteasome (6). PSMD14 has been con rmed to play vital roles in gene ontology and related pathway, including protein stability (7), tumour formation (8), transcriptional regulation (9), double-strand DNA break repair (10), senescence (11), apoptosis and resistance (12), growth and metastasis (6), BMP6 signaling (7), TGF-β signaling (9). Recently, it has been found that PSMD14 is overexpressed in many human cancers, such as HCC, colorectal cancer, multiple myeloma, esophageal squamous cell carcinoma and breast cancer, which are related to the poor prognosis of the patients (6,7,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…PSMD14 stabilizes and inhibits the degradation of GRB2 through deubiquitination, which is an oncoprotein enhances hepatocellular carcinoma growth and metastasis (6). POH1 deubiquitinates the TGF-β receptors and CAV1, contributes to hyperactivation of TGF-β signaling and facilitates hepatocellular carcinoma metastasis, which it negatively regulates lysosome pathway-mediated turnover of TGF-β receptors (9). Other mechanisms of the contribution of PSMD14 in the progression of HCC remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%